2012
DOI: 10.1186/2046-4053-1-46
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of acupuncture research across components of the trauma spectrum response (tsr): a systematic review of reviews

Abstract: BackgroundCo-morbid symptoms (for example, chronic pain, depression, anxiety, and fatigue) are particularly common in military fighters returning from the current conflicts, who have experienced physical and/or psychological trauma. These overlapping conditions cut across the boundaries of mind, brain and body, resulting in a common symptomatic and functional spectrum of physical, cognitive, psychological and behavioral effects referred to as the ‘Trauma Spectrum Response’ (TSR). While acupuncture has been sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 113 publications
(126 reference statements)
0
30
0
Order By: Relevance
“…A review of studies on acupuncture for the treatment of symptoms that are frequently comorbid with PTSD in active duty military returning from combat, reported promising results for acupuncture in reducing the severity of headaches, anxiety, fatigue, sleep disturbances, depression and chronic pain [52]. Acupuncture may be a practical and effective treatment of PTSD in emergency room settings [53].…”
Section: Traditional Chinese Medicinementioning
confidence: 99%
“…A review of studies on acupuncture for the treatment of symptoms that are frequently comorbid with PTSD in active duty military returning from combat, reported promising results for acupuncture in reducing the severity of headaches, anxiety, fatigue, sleep disturbances, depression and chronic pain [52]. Acupuncture may be a practical and effective treatment of PTSD in emergency room settings [53].…”
Section: Traditional Chinese Medicinementioning
confidence: 99%
“…Few publications examined these latter methods; two reviews of acupuncture treatment for PTSD concluded that the evidence base is not strong enough to offer rigorous recommendations. 29,30 With respect to potential consumer-targeted information in the review literature, of special note is the work of Bajor and colleagues (2011), 31 which presented a PTSD update from the Harvard South Shore Program's Psychopharmacology Algorithm Project (http://psychopharm.mobi)-work that aims at developing algorithms for pharmacological treatment options. It should be noted that this algorithm for PTSD was located only via an extensive literature search, not via a consumer-inspired Internet review.…”
Section: The Clinical Evidence Basementioning
confidence: 99%
“…Samueli Institute has performed a comprehensive systematic review of acupuncture for the full spectrum of the wrTSR. 80 Complementary and IM approaches are often of a different nature than symptom-based treatments for isolated manifestations of the wrTSR. These practices can result in healing and recovery of the entire spectrum of symptoms and dysfunction of wrTSR simultaneously.…”
Section: Self-carementioning
confidence: 99%